Academic Senate Minutes 2002-09-19 - Academic Senate:::::::::
Report from Chair. Agenda amended and approved. Minutes amended and approved. Visit from Nancy Kaufman, Planning and Community Development Director for the City of Rohnert Park. Update on Provost Search. Campus Parking Update from Nate Johnson. School Calendar approved. Report from President.